Identifying core beliefs of an intercultural educator: How polyculturalism and group malleability beliefs shape teachers’ pedagogical thinking and practice - Rissanen Inkeri; Kuusisto Elina; McMullen Jake (Springer Science and Business Media B.V., 2025)
Manifestations of educational inequity in diversifying societies have led to a wide acknowledgement of the need to develop all teachers’ competencies to work in the context of diversity. The domain of beliefs and attitudes is generally included as one key component of teachers’ intercultural competence, but there is little consensus over what the core beliefs shaping teachers’ intercultural competencies are. This mixed methods study draws from social psychological research on inter-group relations and explores the role of polyculturalist beliefs and group malleability beliefs in shaping teachers’ orientation to teaching for diversity and social justice. A hypothesized model was tested on survey data from Finnish comprehensive school teachers (N = 231) with structural equation modeling. Findings indicate that polyculturalism, in particular, strongly explains teachers’ teaching for social justice beliefs and enthusiasm for teaching in the context of diversity. Furthermore, we present a case analysis, based on classroom observations and stimulated recall interviews, of how polyculturalism actualizes in one Finnish elementary school teacher’s pedagogical thinking and practice, and discuss the implications of our findings for teacher education and further research.